Comparative physicochemical characterization and sensory profiling of Western Algerian and Polish honeys - Dalila Bereksi-Reguig; Hocine Allali; Salim Bouchentouf; Nessrine Kazi Tani; Grażyna Kowalska; Dariusz Kowalczyk; Jakub Wyrostek; Ewelina Zielińska; Radosław Kowalski (PLoS ONE, 2025)
Background An in-depth analysis was conducted on 37 honey samples from western Algeria representing diverse floral sources—lavender, rosemary, sweet white mustard, thyme, milk thistle, carob, orange, euphorbia, eucalyptus, camphor, jujube, sage, harmal, and multifloral blends. The objective was to evaluate their physicochemical properties and sensory characteristics, with Polish honeys serving as references. Methods Key physicochemical traits were measured, including moisture, pH, free acidity, electrical conductivity, hydroxymethylfurfural (HMF), proline, specific optical rotation, sugar profile (fructose, glucose, sucrose), and colour in CIELAB space (L*, a*, b*, Cab* and hab∘). Sensory evaluation was performed using a five-point hedonic scale (+2 = “like very much” to –2 = “dislike very much”) and an 11-descriptor Check-All-That-Apply (CATA) questionnaire. Results All values satisfied European quality limits (moisture 14.67–20.87%, pH 3.47–5.60, free acidity 8.00–40.33 meq/kg, conductivity 0.16–1.18 mS/cm, HMF 1.79–49.43 mg/kg, sucrose < 5 g/100 g, proline 265.95–1200.66 mg/kg). Polish samples scored higher for taste (+1.22 ± 0.42 vs + 0.18 ± 0.52; p = 0.009) and aroma (+0.72 ± 0.43 vs –0.26 ± 0.36; p = 0.016), whereas colour did not differ (p = 0.459). CATA indicated Algerian honeys were chiefly “mild” and “herbal”, contrasting with Polish “sweet” and “sharp” profiles. Principal-component analysis (PC1 + PC2 ≈ 65% variance) and hierarchical clustering defined three groups: (A) sweet aromatic (all Polish + four Algerian), (B) moderately mild, and (C) sharp–bitter–herbal. Selected Algerian varietals—rosemary (S29) and multifloral (S14)—matched Polish hedonic acceptance, highlighting their premium/exotic market potential. Conclusion Western Algerian honeys exhibit high compositional quality and distinctive sensory signatures, supporting competitiveness in food and health applications.